Thousands of Babies Saved by the Community Empowerment: Free Lending Home Incubator for All - Roihan, Ibnu; Karnadi, Juan; Riantono, Arbi; Artono Koestoer, Raldi (KnE Social Sciences, 2020)
One of the 17 frameworks for the Sustainable Development Goals (SDGs) program concerns a healthy life and encouraging prosperity for everyone. The Indonesian government within the framework of SDGs targeting NMR can decrease to 12 deaths per 1000 births. The existence of an incubator as a premature baby warmer device is very important. But such health facilities are still lacking in the area. The Grashof Portable Home Incubator, which is one of the innovations from Universitas Indonesia, was lent free of charge as one of the product-based community engagement activities from 2012 to the present. It was lent freely to the mothers with newborn babies from lower-class communities. The network of volunteer agents is at the forefront of implementing this activity in many locations in Indonesia. The volunteer agents replace the basic cost production of the incubator so the problem of funds can be overcome. Socialization and collaboration with all levels of society, both individuals and institutions, is carried out so that more premature babies can be helped. Since 2012 this activity has helped more than 3,000 babies in 21 provinces spread over 94 cities/districts. This activity has increased to community empowerment, which directs or indirect helps government programs in reducing infant mortality. Public awareness to help others, especially poor people can make life’s welfare better. Keywords: SDG, People Empowerment, Infant Mortality Rate, Free Lending Incubator, Grashof Incubator